Aptamers 2018 – a conference update. (2018) - Tanner, Julian A; Ismail, Said I; Shigdar, Sarah; DeRosa, Maria C; Hahn, Ulrich; Johnson, Philip E; Suess, Beatrix; McKeague, Maureen
No abstract available